Analisis Historis Perkembangan Islam sebagai Kekuatan Politik di Masa Umar Bin Khattab - Rizki A Ramadhani; Ansar Tohe (Al-Kindi, 2026)
This study examines the transformation of Islam from a religious community into a global political force during the leadership of Umar bin Khattab (634–644 CE). As the second caliph, Umar inherited significant challenges following the Ridda Wars and was required to consolidate internal stability while simultaneously responding to regional geopolitical dynamics. This article aims to analyze Umar's political policies in strengthening the Islamic state, his administrative reforms, and their impact on stability and Islamic civilization. Employing a library research methodology with historical and Islamic political approaches, data were collected through a literature review and analyzed using a descriptive-analytical method. The findings indicate that Umar achieved fundamental breakthroughs by establishing state institutions—such as the *Diwan*, *Baitul Mal*, an independent judicial system, and a separation of powers—that reflected principles of good governance. Massive territorial expansion was managed through calculated diplomatic and administrative strategies. Fiscal policies and equitable wealth distribution fostered socio-economic stability. The study reveals that Umar’s political *ijtihad* (independent legal reasoning) was grounded in the principles of *maqāṣid al-sharī'ah* (the objectives of Islamic law) and demonstrated the flexibility of Islamic law in responding to social change. The relevance of Umar’s political system to modern governance lies in principles of accountability, justice, consultation (*shura*), and bureaucratic professionalism. In conclusion, Umar’s leadership laid the foundation for Islam’s development as a global political power and offers a model of visionary leadership that remains relevant in contemporary contexts. This study recommends further research into the implementation of Umar’s leadership principles within the context of modern governance.